A new genus and species of congrid eel from the Philippines (Anguillliformes: Congridae: Bathymyrinae) - Smith, David G. (Zootaxa, 2018)
Rostroconger macrouriceps sp. nov. is described from a single specimen collected off the east coast of Luzon, Philippines. It is a member of the subfamily Bathymyrinae, differing from all others in the presence of a bony rostrum extending from the anterior end of the snout. The posterior nostril opens into a slit in the upper lip and is not visible externally. The head pores are reduced in size and number; only three pores are present in the infraorbital canal, four in the supraorbital canal, and none in the preopercular or supratemporal canals.